Liberal government's discourse on the 2017-2018 Canada-US cross-border arrivals. (24th September 2019) - Baglay, Sasha
The article examines Canadian government's discourse on the 2017-2018 asylum-seeker border crossings from the US. The analysis reveals presence of mixed messages some of which are in keeping with Canada's image of an open and welcoming country committed to its international obligations, while others reinforce concerns about the arrivals and implicitly suggest that they are taking advantage of the system. These mixed messages are in tension with the Liberal Party's brand of inclusive and open Canada, which obtained popular support at the last federal election and has helped the new Liberal government to differentiate itself internationally.